(untitled) (Communications in Inorganic Synthesis, 2013)
Rhenium(IV) complexes are relatively scarce if compared with those of other oxidation states as Re(V) or Re(VII). It is a 5d3 ion, and usually forms octahedral complexes which are reasonably stable against redox processes and inert to ligand substitution. This is the basis for the preparation of mononuclear species that can act as ligands towards other transition metal ions. For example, complexes containing dicarboxylic ligands, [ReX4(ox)]2–and [ReX4(mal)]2– (X = Cl, Br; ox = oxalato; mal = malonato), or N-donor ligands, [ReCl5(pyz)]– (pyz = pyrazine) have been used as building blocks to construct heteropolynuclear complexes. The different synthetic routes, as well as the designed structures, from discrete binuclear complexes to extended chain-like compounds, are reviewed in this contribution.